2021
DOI: 10.1080/11356405.2021.1949108
|View full text |Cite
|
Sign up to set email alerts
|

Importance of prosodic awareness when learning how to read in primary school students (Importancia de la conciencia prosódica en el aprendizaje de la lectura en estudiantes de educación primaria)

Abstract: Studies in recent years have shown the importance of phonological skills when learning how to read and treating reading difficulties. More recently, research has shown the importance of suprasegmental skills in reading acquisition. However, in spite of this evidence, there is very little research in Spanish aimed at identifying these skills' influence on the reading process. The objective of this study was to analyse the connection between suprasegmental phonological awareness and reading skills in a group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It has been found that people are born with a predisposition to pick up the rhythmic features of the mother tongue (Cutler & Mehler, 1993), which helps to segment the speech continuum into words, facilitating access to lexical representations. The influence of prosodic processing on reading skills has also been demonstrated (Goswami et al, 2002;Gutiérrez-Fresneda et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been found that people are born with a predisposition to pick up the rhythmic features of the mother tongue (Cutler & Mehler, 1993), which helps to segment the speech continuum into words, facilitating access to lexical representations. The influence of prosodic processing on reading skills has also been demonstrated (Goswami et al, 2002;Gutiérrez-Fresneda et al, 2021).…”
Section: Introductionmentioning
confidence: 96%
“…In other words, reading comprehension is understood as a deductive process in which the reader uses the clues in the text to interpret the meaning that the author is trying to convey. Thus readers are not passive subjects, but use their own knowledge by interacting with the text, which allows them to construct new meanings (Gutiérrez-Braojos & Salmerón, 2012;Gutiérrez-Fresneda et al, 2021;Pascual-Gómez & Carril-Martínez, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation